2008
DOI: 10.1111/j.1872-034x.2008.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatic stellate cell activation following Yinchenhao decoction administration to dimethylnitrosamine‐treated rats

Abstract: Yinchenhao administration attenuates liver fibrosis at least in part by inhibiting HSC activation directly, rather than promoting cell apoptosis of activated HSC, and the suppressive activation of Kupffer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…25,28 It is interesting to observe that the a-SMA-positive HSCs in the portal areas and fibrotic septa were free of TUNEL staining. Consistent with our earlier report, 20 this finding is not unexpected and we believe that the following factors might make a contribution to this result. First of all, in the livers treated with 2-week DMN, there was already a peak in the level of apoptotic cells, whereas HSC activation, shown as a-SMA-positive cells, has just begun to be activated.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…25,28 It is interesting to observe that the a-SMA-positive HSCs in the portal areas and fibrotic septa were free of TUNEL staining. Consistent with our earlier report, 20 this finding is not unexpected and we believe that the following factors might make a contribution to this result. First of all, in the livers treated with 2-week DMN, there was already a peak in the level of apoptotic cells, whereas HSC activation, shown as a-SMA-positive cells, has just begun to be activated.…”
Section: Discussionsupporting
confidence: 94%
“…This result was consistent with our earlier reports: a-SMA-positive-HSCs did not co-localize with TUNEL-positive cells in DMN-induced liver fibrosis. 20 Co-localization of TUNEL and a-SMA was also scarcely observed in 6-or 9-week CCL4 rats (Supplementary Figure 5). TUNEL and CD68-double-positive apoptotic KCs (Figure 5a and e) laid closely adjacent to a-SMA þ HSCs (Figure 5d and h).…”
Section: Fas-mediated Cd68-positive Kc Apoptosismentioning
confidence: 95%
See 1 more Smart Citation
“…It has also been reported that YHCT can alleviate obstructive biliary cirrhosis induced by bile duct ligation in rats via inhibiting biliary epithelial cell proliferation and activation 31 . Our previous study also demonstrated that YHCT administration alleviated liver fibrosis via inhibiting hepatic stellate cell (HSC) activation in dimethylnitrosamine-treated rats 32, 33 . Studies by Takahashi et al .…”
Section: Discussionmentioning
confidence: 88%
“…Macrophages are known to play an important role in liver fibrosis and cirrhosis (Heinrichs et al, 2011;Zimmermann et al, 2011;Heymann et al, 2012;Ramachandran et al, 2012), which is a central component of the final, common pathway leading to HSC activation and ECM deposition (Liu et al, 2008(Liu et al, , 2010Chiu et al, 2014). However, the macrophage in kidneys with cirrhosis has not been well studied.…”
Section: Discussionmentioning
confidence: 99%